Penerapan Teori Work Adjustment Untuk Kesesuaian Kerja Dan Kinerja Siswa Dalam Bimbingan Karier Di SMA - Indah Permata Bunda; Ifdil Ifdil; Daharnis Daharnis; Syahrial (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study aims to examine the application of the Theory of Work Adjustment (TWA) in career counseling at SMA Negeri 3 Teluk Meranti, and its impact on students' job fit and performance. TWA is a theory that emphasizes the alignment between an individual's needs and the demands of the work environment. This research uses a descriptive qualitative approach, which delves into the meanings, experiences, and understandings of the subjects regarding the phenomenon and the overall picture. The implementation of TWA at this school is carried out through assessments of students' interests, values, and abilities, as well as guidance on understanding the demands of the workforce. The counseling process includes the use of psychological assessment tools, job simulations, internship programs, and industry visits to help students identify their potential and choose a suitable career path. Additionally, counselors collaborate with the school and parents to create a supportive ecosystem that facilitates students' job readiness. Ongoing evaluations are conducted to provide feedback and support students in overcoming challenges during the adjustment process. The results of the study indicate that the application of TWA can improve students' job fit, readiness for the workforce and overall performance.